Single nocturnal dose of an H2 receptor antagonist for the treatment of duodenal ulcer. Issue 10 (October 1983) - Gledhill, T; Howard, O M; Buck, M; Paul, A; Hunt, R H
Abstract : Twenty four hour intragastric acidity and nocturnal acid output have been measured over five separate 24 hour periods in each of 12 patients with duodenal ulcer receiving either placebo, cimetidine 400 mg bd, cimetidine 300 mg nocte, ranitidine 150 mg bd, or ranitidine 300 mg nocte. In these doses ranitidine was significantly more effective at decreasing intragastric acidity and nocturnal acid output than cimetidine. There was no significant difference between twice daily ranitidine and night time ranitidine or between twice daily cimetidine and night time cimetidine in the reduction of intragastric acidity. Nocturnal acid output was controlled significantly better with ranitidine at night, twice daily dosage of ranitidine, and cimetidine at night, than by the twice daily dosage of cimetidine. It is suggested that a single nocturnal dose of cimetidine or ranitidine should be evaluated in a clinical trial.